Improving the performance of solar membrane distillation processes for treating high salinity feeds: A process control approach for cleaner production. (1st March 2022) - Gil, Juan D.; Roca, Lidia; Zaragoza, Guillermo; Pérez, Manuel; Berenguel, Manuel
Abstract: The treatment of high salinity feeds, for example, brines from other desalination technologies such as reverse osmosis, is becoming one of the sought-after applications of solar membrane distillation processes. One of the most appropriate operating methodologies to carry out these treatments is a batch operation. Nevertheless, throughout this operation, the variability of the salinity in the feed water acts as a disturbance causing the optimal operating conditions required to reduce the process' thermal energy consumption (expressed in kWh/m 3 of freshwater production) to change. To face this issue, this study proposes two real-time optimization control approaches, with energy-saving achievements, based on the extremum-seeking control methodology. The first controller reduces the thermal energy consumption of the membrane distillation module by adapting the feed flow rate according to the level of salinity of the operation. The second one is based on the same idea but tries to search for a trade-off solution among energy consumption and water production. Both approaches are simulated under actual process circumstances using data and a validated model of a pilot plant located at Plataforma Solar de Almería (Spain). The results show how the proposed controllers improve the system's daily operation concerning conventional operational procedures, reducing the system's mean thermal energy consumption up to 35% (from 993.81 kWh/m 3 to 651.52 kWh/m 3 ) in the best case. On the whole, the systematic implementation of the proposed control strategies allows enhancing the sustainability and thermal efficiency of the operation by minimizing unnecessary thermal energy usage. This fact can play a role in solar membrane distillation systems either to lengthen operations or reduce reliance on conventional backup devices in periods with inconstant solar irradiance. Highlights: The batch operation of solar membrane distillation processes is studied. Two model-free controllers are proposed to deal with the operating challenges. The controllers are focused on improving the production and thermal energy consumption. A comparative study is provided with manual operations and a model based controller. The results demonstrate how the thermal energy consumption can be reduced up to 35%.